2015
DOI: 10.3389/fsurg.2015.00021
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Following Hip Arthroscopy – A Systematic Review

Abstract: ContextRehabilitation following hip arthroscopy is an integral component of the clinical outcome of the procedure. Given the increase in quantity, complexity, and diversity of procedures performed, a need exists to define the role of rehabilitation following hip arthroscopy.Objectives(1) To determine the current rehabilitation protocols utilized following hip arthroscopy in the current literature, (2) to determine if clinical outcomes are significantly different based on different post-operative rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 33 publications
0
92
0
11
Order By: Relevance
“…However, reporting of rehabilitation protocol parameters (weight bearing, motion, strengthening and return to sport) was poor [13]. The study concluded that hip arthroscopy rehabilitation guidelines lack high-quality evidence to support a specific protocol.…”
Section: Discussionmentioning
confidence: 99%
“…However, reporting of rehabilitation protocol parameters (weight bearing, motion, strengthening and return to sport) was poor [13]. The study concluded that hip arthroscopy rehabilitation guidelines lack high-quality evidence to support a specific protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative multidisciplinary (MDT) rehabilitation was a critical element to the treatment pathway and is detailed below as recommended by Grzybowski et al, 16 and in line with Wahoff et al's 17 recommendations. All patients gave informed consent.…”
Section: Methods Designmentioning
confidence: 99%
“…Yük verilmeden yapılan mobilizasyon cerrahi sonrası kemik ve kıkırdak dokuyu korumak gerekmiyorsa genelde önerilmemektedir. Kalça fleksör kontraktüründen kaçınmak için primer ve sekonder kalça fleksörlerinin de rehabilitasyonu tavsiye edilir 75 . Konservatif tedavi özellikle genç aktif kiilerde sıklıkla baarısız bulunmutur 9 .…”
Section: Ağırlık Aktarma Yaklaımlarıunclassified